Dental Suction Aerosol: Bibliometric Analysis - Doni Fajar Ramadhan; Azhar Muhammad Fabian; Hendri Maja Saputra (ASEAN Journal of Science and Engineering, 2022)
The rapid spread of the coronavirus had a bad impact on many things, especially on the medical sector. Medical personnel especially dentists are one of the sectors most exposed to the coronavirus because dental procedures produce aerosols and splashes that are contaminated with saliva and blood. This study aimed to investigate the development of research related to dental aerosol suction through the distribution of bibliometrics maps and research trends using VOSViewer. Bibliometric mapping shows the types of publications, publication authors, and publishers of scientific articles. In this study, data collection was carried out from the dimensions.ai site which provides a dataset of scientific articles that have been published in international journals under open source. The keyword was "Dental Suction Aerosol" with the publication year of 2017-2021. Based on studies that have been carried out, the trend of dental suction aerosol research increased during the covid 19 pandemic, the research increase was 31.7% in 2020 and increased by 0.12% in 2021. Based on the publisher’s analysis article, the British Dental Journal is the publisher with the most publications on Dental Suction Aerosol research with 88 publications. The publisher has the most citations in The International Journal Of Environmental Research And Public Health with 628 citations. while based on keyword analysis, keywords related to dental aerosol suction research appeared a lot in 2020, and the most popped-up keywords were "COVID", "Dentist", and "Aerosol".